2016
DOI: 10.1038/srep28836
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture dissection by genome-wide association analysis reveals avian eggshell ultrastructure traits

Abstract: The ultrastructure of an eggshell is considered the major determinant of eggshell quality, which has biological and economic significance for the avian and poultry industries. However, the interrelationships and genome-wide architecture of eggshell ultrastructure remain to be elucidated. Herein, we measured eggshell thickness (EST), effective layer thickness (ET), mammillary layer thickness (MT), and mammillary density (MD) and conducted genome-wide association studies in 927 F2 hens. The SNP-based heritabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 60 publications
3
15
0
Order By: Relevance
“…For example, genetic variations of ovocleidin-116, ovotransferrin and secreted phosphoprotein 1 were linked to the decreased eggshell quality [ 16 ]. Matrix protein genes such as ovalbumin, ovocleidin-116 and ovocalyxin-32 were associated with shell thickness and mammillary layer thickness [ 17 ], while ABCC9, ITPR2, KCNJ8 and WNK1, which are involved in ion transport, were suggested to be the key genes modulating eggshell thickness and effective thickness [ 18 ]. Hence, deteriorations in eggshell ultrastructure and quality in the late phase of production were speculated to be associated with age-related dysregulation of gene expression in uterus.…”
Section: Introductionmentioning
confidence: 99%
“…For example, genetic variations of ovocleidin-116, ovotransferrin and secreted phosphoprotein 1 were linked to the decreased eggshell quality [ 16 ]. Matrix protein genes such as ovalbumin, ovocleidin-116 and ovocalyxin-32 were associated with shell thickness and mammillary layer thickness [ 17 ], while ABCC9, ITPR2, KCNJ8 and WNK1, which are involved in ion transport, were suggested to be the key genes modulating eggshell thickness and effective thickness [ 18 ]. Hence, deteriorations in eggshell ultrastructure and quality in the late phase of production were speculated to be associated with age-related dysregulation of gene expression in uterus.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, two genes, ITPR2 and VIPR1, were identified in the putative selection signature regions, which are possibly related to layer reproductive traits . One recent GWAS study in chicken revealed that the ITPR2 gene was associated with eggshell ultrastructure [ 58 ]. On the other hand, the VIPR1 gene was found to be associated with broodiness [ 59 ], and egg number in chicken [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, genetic variations of ovocleidin-116, ovotransferrin and secreted phosphoprotein 1 were linked to the decreased eggshell quality [16]. Matrix protein genes such as ovalbumin, ovocleidin-116 and ovocalyxin-32 were associated with shell thickness and mammillary layer thickness [17], while ABCC9, ITPR2, KCNJ8 and WNK1, which are involved in ion transport, were suggested to be the key genes modulating eggshell thickness and effective thickness [18]. Hence, deteriorations in eggshell ultrastructure and quality in the late phase of production were speculated to be associated with age-related disturbance in the regulation of gene expression in uterus.…”
Section: Introductionmentioning
confidence: 99%